Performance evaluation of WCDMA systems over fading and interference channels - Ng, Kim Yi (Nanyang Technological University, 2024)
The report presents a performance evaluation of WCDMA (Wideband Code Division Multiple Access) systems operating over fading and interference channels. In this study, the performance of the system is examined in relation to fading due to multipath propagation and interference from co-channel users. In addition to varying levels of interference, fading, and user mobility, simulation results are presented for different scenarios. A few performance metrics were assessed, including the bit error rate, outage probability, and capacity. The performance of a system is also impacted by techniques for power control and diversity. In the study, power control and diversity techniques proved valuable as techniques for improving the performance of WCDMA systems under conditions of fading and interference.